2008
DOI: 10.1143/apex.1.053001
|View full text |Cite
|
Sign up to set email alerts
|

Focusing Characteristics of Double-Gated Field-Emitter Arrays with a Lower Height of the Focusing Electrode

Abstract: In order to control electric field relaxation at the tips of practical emitters, we found that volcano-structured double-gated field emitter arrays (VDG-FEAs) could be improved by placing the focusing electrode 470 nm below the electron extraction electrode. We demonstrated that this approach enables excellent endurance in terms of focusing potential, and confirmed its superior focusing characteristics. Even under strong focusing operation at a focusing electrode voltage of 5 V, this VDG-FEA maintained the ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…[1] To solve such the problem, we have reported the other approach that uses the focusing electrode located below the extraction gate electrode in a volcano structure. [2,3] However, we observed that some electrons cannot penetrate the potential barrier formed by the focusing electrode potential under strong focusing conditions. These electrons go back to the extraction gate electrode.…”
Section: Introductionmentioning
confidence: 78%
“…[1] To solve such the problem, we have reported the other approach that uses the focusing electrode located below the extraction gate electrode in a volcano structure. [2,3] However, we observed that some electrons cannot penetrate the potential barrier formed by the focusing electrode potential under strong focusing conditions. These electrons go back to the extraction gate electrode.…”
Section: Introductionmentioning
confidence: 78%
“…FEAs have also been studied as the cathode for a compact free electron laser with sub-nanometer wavelength [8]: FEAs can be competitive with the state-of-the-art photocathode [9], [10] when the angular spread Δθ of individual beams is reduced below ~1° while keeping the average current density above ~1 kA cm -2 as demonstrated in single-gate devices [11]. Δθ can be reduced in double-gate FEAs by applying a negative bias V c to G c with magnitude comparable to the positive electron extraction bias V ex applied between G ex and emitters as reported in the literatures [1][2][3][4][5][6][7]. However, since the negative V c can reduce the electric field F apx at the tip-apex and the emission current, the optimization of the device structure minimizing the influence of V c on F apx is crucial.…”
Section: Introductionmentioning
confidence: 95%
“…V ACUUM devices are excellent candidates for harshenvironment and high-frequency electronics thanks to their radiation hardness and scattering-free electron transport [1]. Si and metal field emitters (FEs) have been developed into mature technologies in recent years [2]- [5]. III-Nitride semiconductors promise to further improve FEs thanks to their tunable electron affinities [6], [7].…”
Section: Introductionmentioning
confidence: 99%